MANAJEMEN SUNGAI KLAWING UNTUK KELESTARIAN IKAN SPESIES ASLI - Ayesha Hafizh Gunara; Siti Rukayah (UNIVERSITAS PGRI MADIUN, 2019)
This study aims to determine the water quality in the Klawing River, riparian vegetation, native and introduced fish, utilization, the presence of pollutant resources, fishing practices, and regional regulations related to the Klawing River. Research methods by surveying and searching libraries. The results showed that the condition of water quality in the Klawing River upstream was in good condition, while the middle and downstream parts had decreased. Riparian vegetation in the upper reaches is still dominated by trees compared to the middle and downstream. Along the Klawing River, there are still many locations that have the potential for erosion. There are 23 species of fish found along the Klawing River. Among these species, there are 16 species of native fish species and 7 species of introduced fish species. The source of pollution in the Klawing River comes from liquid waste and solid waste. Fishing is done by using fishing gear such as fishing rods, nets, stone cages, but there are still those who use drugs and stroom. Existing regulations on the Klawing River only refer to government regulations governing the river because it does not yet have a special PERDA.